Load Transfer Distance Calibration of a Coal Panel Scale Model: a Case Study - Mark K. Larson (International Conference on Ground Control in Mining, 2012)
Calibration of LaModel for deep coal mines begins with adjustment of overburden stiffness for load transfer distance. This calibration determines whether mining induced stresses are concentrated in the immediate abutment of the gob, or spread over a wider area. In the absence of site information, an empirically-based estimate is often used. Where data is available, a recommended calibration procedure can be followed, as is done in this case study at a deep western longwall mine, with minor modifications and extensions. In this case, data sources included borehole pressure cells, flatjacks installed in series with support Cans, and observed changes in ground conditions. Calibration was based on the first detection of mining-induced stress from the advancing longwall. Detection was found to depend on the type and sensitivity of measurement. Borehole pressure cell data with a 20-psi-increase detection threshold were chosen as the standard, in accord with data used in deriving empirical relationships. Application of this standard produced a load transfer distance estimate roughly four times the empirical relationship developed by Peng and Chiang (1984). This is a significant deviation with important implications for panel design at this site. Data from flatjacks, ground condition observations, and borehole pressure cells with higher threshold values, were tightly clustered and show load transfer distances from two to four times empirical guidance. Ratios between various measurements can be used to adjust measurements to the standard (although they may depend on mine geology). Once established, ratios can be used to adjust estimates, say from support flatjacks or ground observations, to the standard, where borehole pressure cell data is not available.`